Schwannoma arising in a lymph node mimicking metastatic pulmonary carcinoma - Kamiyoshihara, Mitsuhiro (Respir Med Case Rep, 2018)
Schwannomas commonly arise in the torso, extremities, and mediastinum. However, no interlobar lymph node (#11i) lesions have ever been reported. This is a thought-provoking case, because it involved a schwannoma arising in a lymph node mimicking metastatic pulmonary carcinoma. A 72-year-old man was diagnosed with primary pulmonary carcinoma, and 18F-fluorodeoxyglucose (FDG) positron emission tomography demonstrated high FDG uptake in the primary lesion and in #11i, which suggested metastasis (clinical stage IIA). A right lower lobectomy with lymph node dissection was performed. Fortunately, the enlarged #11i was a schwannoma and not metastasis. The take-home message is “a patient with multiple neuromatosis tends to have schwannomas throughout the body”.